Leadership Style And Employee Performance: A Study Of Transformational And Transactional Leadership Style In Deposit Money Banks In Nigeria (Case Study Of Zenith Bank) (Journal of Finance, Business and Management Studies, 2026)
This study explores the impact of transformational and transactional leadership styles on employee performance within Zenith Bank branches in Lagos State. A quantitative research methodology rooted in a positivist philosophy was employed. Data were collected from a conveniently selected sample of 50 employees across three branches that were chosen randomly. Employee performance was the dependent variable, while transformational and transactional leadership styles were the independent variables. The findings reveal that both leadership styles significantly influence employee performance, with transformational leadership demonstrating a more profound impact. These results highlight the importance of adopting transformational leadership to foster higher levels of employee commitment and performance.Keywords: Employee Performance; Leadership Style; Transformational Leadership; Transactional Leadership